(untitled) (Altre Modernità, 2020)
The neo-historical novel – literary genre which combines the use of documents, testimony and fiction – offers an ideal case study of what Francesco Orlando, in the early Seventies, called the "formal return of the repressed". Proof of this is the emergence, within the texts, of memorial waste which has been ousted from cultural memory. This article will focus on Des hommes (2009) by Laurent Mauvignier and Le rondini di Montecassino (2010) by Helena Janeczek, two récits de filiation that deal with paternal silence originated by historical trauma. Facing the double censorship of both official and familial discourse, memorial waste turns into a fundamental tool for the writers involved. These marginal sources not only become the main subject of their narratives, but they also directly affect the writing process, as shown by the analysis of narrative models (inner monologue, polyphonic epic), textual spaces and rhetorical devices (blancs, mise en abyme). I will contend that, through different approaches, both texts enable a centripetal movement by which what has been previously marginalized seeks to find its place within the cultural memory.